KAJIAN PENURUNAN TANAH TIMBUNAN PENYEBAB KERETAKAN STRUKTUR RIGID PAVEMENT DENGAN MENGGUNAKAN METODE ASAOKA (Studi Kasus Proyek Pembangunan Jalan XYZ) - Supriyadi Supriyadi; Junaidi Junaidi; Anis Wahyuni; M. Rifqi Mubarok (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
Rigid pavement work on the XYZ Road Construction Project experienced a problem, namely the occurrence of cracks in the rigid pavement structure above the box culverts under which soil improvement was carried out using embankment soil. The purpose of this study is to analyze the factors that cause settlement of the embankment that causes the rift of the rigid pavement structure on box culverts built on embankment soil so that the results can be used as a reference for handling or repairing rigid pavement work on box culverts with a structure piled up soil in subsequent segments. From the results of the analysis it can be seen that the process of casting rigid pavement was carried out at two points, namely Point 1 and Point 2 where after casting the rigid pavement, the subgrade beneath it still experienced a decrease of 10 mm and 6 mm. This decline occurred for up to 3 months and caused cracks in the rigid pavement structure above it. This is due to the difference in settlement of the box culvert which was initially assumed not to have decreased again with the surrounding embankment which was still experiencing settlement. In addition, the results of the analysis show that the rigid pavement design uses a single reinforcement so that the capacity of the concrete (Mu) is less than the weight of the concrete itself which causes the concrete to crack.